Activity and bioavailability of food protein‐derived angiotensin‐I‐converting enzyme–inhibitory peptides. Issue 2 (2nd February 2021) - Xue, Lu; Yin, Rongxin; Howell, Kate; Zhang, Pangzhen
Abstract: Angiotensin‐I‐converting enzyme (ACE) inhibitory peptides are able to inhibit the activity of ACE, which is the key enzymatic factor mediating systemic hypertension. ACE‐inhibitory peptides can be obtained from edible proteins and have the function of antihypertension. The amino acid sequences and the secondary structures of ACE‐inhibitory peptides determine the inhibitory activities and stability. The resistance of ACE‐inhibitory peptides to digestive enzymes and peptidase affect their antihypertensive bioactivity in vivo . In this paper, the mechanism of ACE‐inhibition, sources of the inhibitory peptides, structure–activity relationships, stability during digestion, absorption and transportation of ACE‐inhibitory peptides, and consumption of ACE‐inhibitory peptides are reviewed, which provide guidance to the development of new functional foods and production of antihypertensive nutraceuticals and pharmaceuticals.